DESIGN, OPTIMIZATION, AND STATISTICAL EVALUATION OF ORAL RECONSTITUTED SUSPENSION OF CLARITHROMYCIN USING ION-EXCHANGE RESINS - S, KOMAL; N, HARIKRISHNAN (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objectives: The objective of the present study is taste masking of bitter clarithromycin using Indion 204, Indion 234, and Tulsion 335 as ion-exchange resins, which forms insoluble complexes, inhibiting the drug release in saliva as ion-exchange resins are cross-linked polymers, water-insoluble that contains salt-forming groups in repeating positions on the polymer chain. Drugs that are bitter and cationic get adsorbed onto weak cationic exchange resins of carboxylic acid functionality such as Indion 204, Indion 234, and Tulsion 335 to form non-bitter complexes. Methods: The drug-resin complex loading process was optimized for the resin content, activation, swelling time, stirring time, influence of pH, and temperature for maximum drug loading and the formed complex was evaluated by differential scanning calorimetry (DSC) to confirm complex formation. The drug-resin complex was also characterized by their micromeritic and rheological properties. These complexes were used to prepare oral reconstituted suspensions and the taste was evaluated. The formulation was evaluated for various parameters such as sedimentation volume, pH, redispersibility, viscosity, drug content, and in vitro drug release. Results: Acid-activated resins comprising Indion 204, Indion 234, and Tulsion 335 with the drug:resin ratio of 1:2, stirred in a solution of pH 7–8 at 70° for 6 h had a maximum drug loading and masked the bitter taste of clarithromycin. DSC of the drug-resin complex (DRC) revealed that there was interaction leading to complex formation. The drug-resin complex was formulated into suspension formulations (S1-S9) and evaluated. Various parameters were found to be within permissible limits. Formulations S3, S6, and S9 containing 1:2 ratios of the drug-resin complex of Indion 204, Indion 234, and Tulsion 335 revealed maximum taste masking. This was further confirmed by treatment of taste evaluation scores obtained from the volunteers by ANOVA, Dunnett’s multiple comparison test, and Tukey’s multiple comparison test. All the three optimized formulations had a significant difference of p<0.001 when compared to control S10. S6 formulation was widely accepted. Conclusion: Ion-exchange complexation could efficiently mask the bitter taste of clarithromycin and achieve palatable taste suitable for pediatric use.